2020
DOI: 10.15288/jsads.2020.s19.97
|View full text |Cite
|
Sign up to set email alerts
|

Similarities Between Alcohol and Tobacco Advertising Exposure and Adolescent Use of Each of These Substances

Abstract: Objective: Underage alcohol use is a major public health problem and substantial corporate money supports alcohol advertising across multiple venues. A diverse research literature demonstrates that adolescent exposure to such advertising is associated with drinking attitudes and behavior, but no scientific body has determined these associations to be causal. The objective of this study was to assess the association between alcohol advertising and teen drinking in the context of the “Analogy” crite… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
14
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 54 publications
1
14
0
1
Order By: Relevance
“…In contrast, those who perceived a greater distance from marijuana shops but who reported greater exposure to marijuana-related advertisements were more likely to report intentions to use marijuana. This finding supports other scholars' conclusions that exposure to substance use advertising predicts adolescents' use of the drug (Sargent & Babor, 2020;Weitzman & Lee, 2020). Further, it suggests that while living far away from a marijuana retailer may serve as a protective factor, this protection is mitigated when the individual is exposed to marijuana advertising.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…In contrast, those who perceived a greater distance from marijuana shops but who reported greater exposure to marijuana-related advertisements were more likely to report intentions to use marijuana. This finding supports other scholars' conclusions that exposure to substance use advertising predicts adolescents' use of the drug (Sargent & Babor, 2020;Weitzman & Lee, 2020). Further, it suggests that while living far away from a marijuana retailer may serve as a protective factor, this protection is mitigated when the individual is exposed to marijuana advertising.…”
Section: Discussionsupporting
confidence: 87%
“…For example, point of sale advertisements for e-cigarettes in stores near schools was found to contribute to youth's use of e-cigarettes (Giovenco, Casseus et al, 2016). Weitzman and Lee (2020) applied The Bradford Hill criteria, which is a set of principles that help identify a causal relationship, to the existing literature and concluded that exposure to alcohol and tobacco advertising was predictive of youths' subsequent use of the drugs. Similarly, Sargent and Babor (2020) determined adolescents' initiation of alcohol use and binge drinking were caused, at least in part, by their exposure to alcohol advertising.…”
Section: Effects Of Substance Marketing and Media Exposurementioning
confidence: 99%
“…As seen, values that are important for adolescents are at play within SNSs’ use (e.g., friendship), and gimmicks that are developed by the SNSs’ platforms based on these values (e.g., Snapstreak) to encourage adolescents to use their profile regularly should be questioned. Studies have documented such impacts and advocated for the need to allow adolescents to master the use of SNSs [ 2 , 5 ]. The adolescents from our focus groups were making some links between the influence of advertisement or product placement over their behaviour (e.g., buying clothes advertised), but did not seem to be fully aware of the many variables at stake regarding the influence of the content of media over their health.…”
Section: Discussionmentioning
confidence: 99%
“…Concerns regarding A+T posts displayed on social networking sites (SNSs) for example Snapchat, Facebook, Instagram, etc. have been researched internationally, particularly when it comes to their influence on adolescents’ behaviour towards these substances [ 1 , 2 , 3 , 4 , 5 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation